Pengaruh Intellectual Capital Dan Kepemilikan Manajerial Terhadap Nilai Perusahaan Dengan Financial Distress Sebagai Variabel Intervening - Asmawati Hamiruddin; Herman Darwis; Meliana Meliana (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
The aim of this research is: To analyze and obtain empirical evidence of the direct and indirect influence of intellectual capital and managerial ownership on company value with financial distress as an intervening variable. The population used in this research is manufacturing companies listed on the Indonesian Stock Exchange for the 2017-2021 period. Sampling was based on purposive sampling. The type of data used in this research is qualitative data and data analysis using the EVIEWS 9 application. The methods used are panel data regression models and path analysis. The results of this research show that intellectual capital and managerial ownership have no direct or indirect influence on company value through financial distress as an intervening variable.